2017
DOI: 10.3389/fnhum.2017.00137
|View full text |Cite
|
Sign up to set email alerts
|

fNIRS Studies on Hemispheric Asymmetry in Atypical Neural Function in Developmental Disorders

Abstract: Functional lateralization is highly replicable trait of human neural system. Many previous studies have indicated the possibility that people with attention-deficits/hyperactivity-disorder (ADHD) and autism spectrum disorder (ASD) show hemispheric asymmetry in atypical neural function. However, despite the abundance of relevant studies, there is still ongoing controversy over this issue. In the present mini-review, we provide an overview of the hemispheric asymmetry in atypical neural function observed in fNIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 66 publications
0
19
0
3
Order By: Relevance
“…This observation might confirm atypical brain laterality observed earlier in adult patients with ADHD (right hemisphere deficit) (Mohamed et al 2015). Moreover, a recent review of fNIRS studies has reported that right hemisphere asymmetry in atypical neuronal function was found in children with ADHD (Doi and Shinohara 2017). Another longitudinal study has shown that healthy children progressively developed normal lateralisation of the right frontal cortex and left occipital cortex during development, although this normal lateralisation would be disrupted for ADHD children (Shaw et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation might confirm atypical brain laterality observed earlier in adult patients with ADHD (right hemisphere deficit) (Mohamed et al 2015). Moreover, a recent review of fNIRS studies has reported that right hemisphere asymmetry in atypical neuronal function was found in children with ADHD (Doi and Shinohara 2017). Another longitudinal study has shown that healthy children progressively developed normal lateralisation of the right frontal cortex and left occipital cortex during development, although this normal lateralisation would be disrupted for ADHD children (Shaw et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…TH was proposed as a marker because this rate-limiting enzyme of the dopamine synthesis is down-regulated in the PFC of SHRs (Viggiano et al 2004) and human ADHD patients, and dopamine is essential for proper functioning of the PFC (Arnsten 2009). As many of the brain abnormalities were reported in one of the brain hemispheres only (Rubia et al 1999; Shaw et al 2009; Silk et al 2016; Doi and Shinohara 2017), both left and right hemispheres were investigated. Considering that brain abnormalities associated with ADHD manifest in pre-pubertal SHRs (5-week-old) and they often disappear in maturing SHRs (10-week-old) (Hsu et al 2010), any abnormalities in studied biologically active substances contents due to ADHD should be observed before puberty.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44][45] Functional near-infrared spectroscopy, which measures changes in the concentration of oxygenated and deoxygenated haemoglobin, is less sensitive to movement artefacts, which makes it particularly advantageous for the study of individuals with ADHD. In a recent review, 46 most of the studies reported an atypical pattern of oxygenated haemoglobin more prominently in the right hemisphere during the execution of inhibition, attentional control, verbal fluency, facial expression recognition, and affective prosody processing tasks in children with ADHD. Hypoactivation was particularly found in right frontal regions, but also in the temporal and parietal cortices in these children and in bilateral frontal regions in adults.…”
Section: Haemodynamic Measuresmentioning
confidence: 99%
“…Hypoactivation was particularly found in right frontal regions, but also in the temporal and parietal cortices in these children and in bilateral frontal regions in adults. 46…”
Section: Haemodynamic Measuresmentioning
confidence: 99%
“…B. subkortikale Strukturen untersuchen. In einem kurzen Übersichtsartikel hielten die Autoren fest, dass die meisten fNIRS-Studien mit sehr unterschiedlichen Paradigmen ein atypisches Muster von oxygeniertem Hämoglobin vor allem in der rechten Hirnhemisphäre zeigen [64]. Diese Studien zeigten verminderte Aktivität im rechten präfrontalen Kortex, im Gyrus frontalis inferior und medius, aber auch in temporalen und parietalen Cortices.…”
Section: Hämodynamische Bildgebungunclassified